2014
DOI: 10.4049/jimmunol.1400238
|View full text |Cite
|
Sign up to set email alerts
|

Lipin-1 Integrates Lipid Synthesis with Proinflammatory Responses during TLR Activation in Macrophages

Abstract: Lipin-1 is a Mg2+-dependent phosphatidic acid phosphatase involved in the de novo synthesis of phospholipids and triglycerides. Using macrophages from lipin-1–deficient animals and human macrophages deficient in the enzyme, we show in this work that this phosphatase acts as a proinflammatory mediator during TLR signaling and during the development of in vivo inflammatory processes. After TLR4 stimulation lipin-1–deficient macrophages showed a decreased production of diacylglycerol and activation of MAPKs and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(106 citation statements)
references
References 42 publications
4
84
0
5
Order By: Relevance
“…We propose that the sustained production of lipids (such as lipin-1 generated diacylglycerol) within foam cells leads to the inadvertent activation of signaling cascades that result in macrophage pro-inflammatory cytokine responses. Furthermore, the observation that lipin-1 seems to more significantly contribute to oxLDL-elicited pro-inflammatory responses than that observed for LPS stimulation 16 suggests that targeting lipin-1 enzymatic activity may reduce atherosclerotic inflammation without rendering individuals susceptible to bacterial infection. Whether the modulation of lipin-1 activity can provide therapeutic benefits for the treatment of atherosclerosis and CVD will be the focus of future research.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…We propose that the sustained production of lipids (such as lipin-1 generated diacylglycerol) within foam cells leads to the inadvertent activation of signaling cascades that result in macrophage pro-inflammatory cytokine responses. Furthermore, the observation that lipin-1 seems to more significantly contribute to oxLDL-elicited pro-inflammatory responses than that observed for LPS stimulation 16 suggests that targeting lipin-1 enzymatic activity may reduce atherosclerotic inflammation without rendering individuals susceptible to bacterial infection. Whether the modulation of lipin-1 activity can provide therapeutic benefits for the treatment of atherosclerosis and CVD will be the focus of future research.…”
Section: Resultsmentioning
confidence: 96%
“…Macrophages require lipin-1 for PGE 2 and pro-inflammatory cytokine production in response to LPS and the intracellular bacteria Francisella tularensis 1516 . We demonstrate here that short-term oxLDL treatment (24 hours) fails to elicit pro-inflammatory cytokine responses, in agreement with work by Spann et.al, who demonstrated that cholesterol uptake by macrophages results in an anti-inflammatory macrophage phenotype 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherent macrophages were then used for experimentation. When mice were treated with LPS, the animals were intraperitoneally injected with LPS at a dose of 5 mg/kg for 6 hr, after which the animals were euthanized with ketamine (100 mg/kg)/xylacine (10 mg/kg) and cervical dislocation (Meana et al, 2014). All the protocols and procedures were approved by the Institutional Animal Care and Usage Committee of the University of Valladolid, and are in accordance with the Spanish and European Union guidelines for the use of experimental animals.…”
Section: Experimental Procedures Cell Isolation and Culture Conditionsmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) and pro-inflammatory cytokines such as TNF-α, IL-1β, and IFN-γ decrease lipin-1 mRNA and protein, but not lipin-2 or lipin-3,in mouse adipose tissue and in cultured 3T3-L1 adipocytes (6062). Paradoxically, a recent study has revealed an unexpected role for lipin-1 as a mediator of macrophage proinflammatory activation (63). Upon Toll- Like-Receptor (TLR4) stimulation of macrophages from lipin-1-deficient animals and human macrophages deficient in the lipin-1 enzyme, the generation of proinflammatory cytokines known to be involved in inflammatory process, was reduced, suggesting that lipin-1-PAP acts as a proinflammatory mediator downstream of TLR signaling and during the development of inflammatory processes in macrophage (63).…”
Section: Role Of Lipin-1 In Afldmentioning
confidence: 99%